Existence of solutions for nth-order nonlinear differential boundary value problems by means of fixed point theorems. (August 2018) - Cabada, Alberto; Saavedra, Lorena
Abstract: This paper is devoted to prove the existence of one or multiple solutions of a wide range of nonlinear differential boundary value problems. To this end, we obtain some new fixed point theorems for a class of integral operators. We follow the well-known Krasnoselskiĭ's fixed point Theorem together with two fixed point results of Leggett–Williams type. After obtaining a general existence result for a one parameter family of nonlinear differential equations, are proved, as particular cases, existence results for second and fourth order nonlinear boundary value problems.